Genotype X Season Interaction Effects on the Laying Mortality Rates of the Nigerian Local Chicken, the Barred Plymouth Rock and Their Crosses - Mmereole, F.U.C.; Bratte, L.; Omeje, S.I. (International Journal of Poultry Science, 2007)
An experiment was conducted to compare the effects of genotypes, seasons and genotype x season interactions on the laying mortality rates in the Nigerian local chickens (LC), the Barred Plymouth Rock (BR) and their F1 cross-progenies. The parent-stock was separated into four mating groups to produce four genotypes (G):- BR x BR (G1), LC x LC (G2) BR x LC (G3) and LC x BR (G4). The experiment was conducted during the dry and rainy seasons. Weekly mortality rates were computed for 24 weeks of lay. The data generated from the experiment were subjected to a 2 x 4 x 6 factorial analysis using S.A.S package. The results indicate that G2 and G3 with mortality rates (MR) of 1.91 and 3.28 respectively performed better than G1 and G4 with MR of 5.17 and 5.62 respectively. The results further indicate that experimental chickens performed better during the dry season (MR =3.08) than during the rainy season (MR=4.91). However, it was observed that the genotype x season interaction did not produce any significant effect on the mortality rates of the chickens. The results from this experiment underscore the need to improve the livability of the laying chickens by developing genotypes which are more tolerant with the local environment and the prevailing season. Based on the results, it was concluded that the mortality rates in the laying chicken can be reduced by crossing the exotic chicken with the local chicken and that a building system could be designed which can help reduce mortality rates during rainy seasons.